2018
DOI: 10.1016/j.cell.2018.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Intrinsic Control of Interneuron Migration Drives Cortical Morphogenesis

Abstract: SummaryInterneurons navigate along multiple tangential paths to settle into appropriate cortical layers. They undergo a saltatory migration paced by intermittent nuclear jumps whose regulation relies on interplay between extracellular cues and genetic-encoded information. It remains unclear how cycles of pause and movement are coordinated at the molecular level. Post-translational modification of proteins contributes to cell migration regulation. The present study uncovers that carboxypeptidase 1, which promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 42 publications
0
61
0
Order By: Relevance
“…The reduced number of S-phase cells in the cortex could indicate that the cell cycle length of progenitor cells is affected, as has been reported for other neural populations (Vilar et al, 2006;Zanin et al, 2016;Zhang et al, 2009). Furthermore, it has recently been reported that the proliferation of pyramidal neuron progenitors is controlled by the rate of cortical invasion of migrating interneurons, with higher levels of proliferation observed if more interneurons invade at the same time (Silva et al, 2018). Similarly, a mouse strain harboring a deletion of the transcription factor Nkx2.1, a master regulator of interneuron development, showed attenuated proliferation of pyramidal neuron progenitors, consistent with the idea that the number of pyramidal neurons is fine-tuned and adjusted during development according to the number of invading interneurons, thereby ensuring the proper formation of local networks (Butt et al, 2008;Silva et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The reduced number of S-phase cells in the cortex could indicate that the cell cycle length of progenitor cells is affected, as has been reported for other neural populations (Vilar et al, 2006;Zanin et al, 2016;Zhang et al, 2009). Furthermore, it has recently been reported that the proliferation of pyramidal neuron progenitors is controlled by the rate of cortical invasion of migrating interneurons, with higher levels of proliferation observed if more interneurons invade at the same time (Silva et al, 2018). Similarly, a mouse strain harboring a deletion of the transcription factor Nkx2.1, a master regulator of interneuron development, showed attenuated proliferation of pyramidal neuron progenitors, consistent with the idea that the number of pyramidal neurons is fine-tuned and adjusted during development according to the number of invading interneurons, thereby ensuring the proper formation of local networks (Butt et al, 2008;Silva et al, 2018).…”
Section: Discussionmentioning
confidence: 71%
“…Furthermore, it has recently been reported that the proliferation of pyramidal neuron progenitors is controlled by the rate of cortical invasion of migrating interneurons, with higher levels of proliferation observed if more interneurons invade at the same time (Silva et al, 2018). Similarly, a mouse strain harboring a deletion of the transcription factor Nkx2.1, a master regulator of interneuron development, showed attenuated proliferation of pyramidal neuron progenitors, consistent with the idea that the number of pyramidal neurons is fine-tuned and adjusted during development according to the number of invading interneurons, thereby ensuring the proper formation of local networks (Butt et al, 2008;Silva et al, 2018). Therefore, the phenotype observed in Nestin-Cre p75 in/in mice may reflect a combination of cell-autonomous and non-cell-autonomous effects, resulting in the impaired survival and proliferative capacity of cortical progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified mutations in several genes encoding cytoskeletal motors and their associated molecules as the causes of these disorders (Manzini and Walsh, 2011;Cooper, 2013;Moon and Wynshaw-Boris, 2013;Buchsbaum and Cappello, 2019). These studies have expanded our knowledge of the roles of cellular signaling, including post-translational modifications of cytoskeletal molecules, in neuronal migration (Silva et al, 2018(Silva et al, , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The centrosome is tethered to the nucleus through a perinuclear cage of microtubules and acts to generate a forward pulling force on the nucleus during nucleokinesis (Bellion et al, 2005; Umeshima et al, 2007). Disruptions in centrosome motility and positioning are thought to underly nucleokinesis defects seen in other studies of neuronal migration (Luccardini et al, 2013; Luccardini et al, 2015; Silva et al, 2018; Solecki et al, 2009). Since we found significant defects in nucleokinesis in migrating MGE interneurons, we sought to determine if centrosome dynamics were also disrupted during JNK inhibition.…”
Section: Resultsmentioning
confidence: 91%
“…Failure to coordinate these cellular and subcellular events can alter cortical interneuron migration and impair the development of cortical circuitry, which may underlie severe neurological disorders such as autism spectrum disorder, schizophrenia, and epilepsy (Hildebrandt et al, 2011; Kato and Dobyns, 2005; Meechan et al, 2012; Volk et al, 2015). While progress has been made on elucidating the complex molecular mechanisms underlying nucleokinesis and leading process branching (Baudoin et al, 2012; Godin et al, 2012; Silva et al, 2018; Tsai and Gleeson, 2005), the intracellular signaling pathways that regulate these cellular mechanisms remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%